Role of Clinical Pharmacist in Medication Management of Inotropes and Vasopressors in Intensive Care Unit - Sebastian, Sneha; Justin, Sherine; PS, Athira; Daniel, Lidhu; Sathyamurthy, G.; Menaka, K.; Thangavel, Sivakumar (Indian Journal of Pharmacy Practice)
Background: Medication management of inotropes and vasopressors are essential in critically ill patients, as it is considered as important life-saving medications. The present study was carried out to understand the effect of these drugs on unstable patient and identifying drug-related problems like significant interactions, adverse effects, incompatibility and its factors. Methods: A prospective observational study was carried out in the medical, surgical Intensive Care Unit for a period of 6 months. All the interventions and drug related problems were categorized based on the Pharmaceutical Care Network Europe. Results: Out of 150 study population male patients were more and the majority of patients were from the age group of 60-80 years (56.66%). Most of the admissions were due to septic shock (50%). Noradrenaline (64%) were mostly prescribed. This study illustrates that there is an increased effect of drugs on hemodynamic instability based on mean arterial pressure and heart rate. By comparing before and after administration there was a significant (P<0.0001) increased effect in unstable patients. Among 108 significant drug interactions, dobutamine (50.92%) shows high in frequency. Tachycardia (18.66%) is the most common adverse drug reactions. Among 11 incompatible combinations, Dobutamine+pantoprazole (30.18%) shows the highest and the factors affecting the incompatibility of drugs such as diluents used, rate and duration of infusion, pH of drug solution. Out of 126 recommendations given by clinical pharmacist, 70 problems were solved. Conclusion: Interventions made by a clinical pharmacist improves medication safety in critically ill patients by the safe and effective use of inotropes and vasopressors.
Keywords: Mean arterial pressure; Heart rate; Drug interaction; Adverse drug reaction; Incompatibility; Interventions.